Antibacterial tetraoxygenated xanthones from the immature fruits of Garcinia cowa - Chiramet Auranwiwat (2018)
A phytochemical investigation of the acetone extract from the immature fruits of Garcinia cowa led to the isolation of two novel tetraoxygenated xanthones, garcicowanones A (1) and B (2), together with eight known tetraoxygeanted xanthones. Their structures were determined by spectroscopic analysis. All isolated compounds were evaluated for their antibacterial activity against Bacillus cereus TISTR 688, Bacillus subtilis TISTR 008, Micrococcus luteus TISTR 884, Staphylococcus aureus TISTR 1466, Escherichia coli TISTR 780, Pseudomonas aeruginosa TISTR 781, Salmonella typhimurium TISTR 292 and Staphylococcus epidermidis ATCC 12228. α-Mangostin showed potent activity (MIC 0.25-1 μg/mL) against three Gram-positive strains and garcicowanone A and β-mangostin exhibited strong antibacterial activity against B. cereus with the same MIC values of 0.25 μg/mL. © 2014 Elsevier B.V. All rights reserved.